Regulation of stability studies to enhance the efficiency of drug registrations to regulatory authorities - Mohammad Sajjad Khan; Nabila Akhtar (Archives of Global Professionals, 2015)
Stability testing is an important tool to assess the quality of drug substances and products which may vary with time under influence of variety of factors such as temperature, humidity, and light. Stability studies of drugs are designed according to the climatic zones to establish a retest period for active drug substance or a shelf life for the finished product as well as to recommend the storage conditions. The strict regulatory requirements on designing, performing evaluating stability study to claim the expiry date, and shelf life of drug products are based on a series of regulatory requirements and advisory guidelines that have been developed by regulatory authorities of US, Europe, and Japan which; were harmonized through the development of the International Conference on Harmonization (ICH) procedures. To assess the stability of drug substances and products, the design and conduct of stability studies, defining relevant thresholds for impurities testing is required with a current good manufacturing practice-based risk management approach to achieve a robust stability of pharmaceutical dosage forms. There are relevant requirements that cover new drug substances and products as well as new dosage forms containing existing active ingredients and vice versa.